Conductive slurry, conductive electrode, preparation method of conductive slurry and conductive electrode, and crystalline silicon solar cell

By reasonably adjusting the composition and structure of glass powder and silver powder in conductive paste, the problem of difficulty in reducing silver ions in p-poly TOPCon crystalline silicon solar cells is solved, and the low resistance silver silicon contact structure is realized, and the efficiency of solar cells is improved.

CN120221152APending Publication Date: 2025-06-27SOLAMET ELECTRONIC MATERIALS (DONGGUAN) CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510278858.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

The conductive paste of existing p-poly TOPCon type crystalline silicon solar cells affects the photoelectric conversion efficiency of crystalline silicon solar cells. It is mainly because silver ions are difficult to reduce on p-poly to form a large amount of silver crystals, resulting in too high electrical contact resistance between the electrode structure and p-poly.

Method used

A conductive paste is provided, and its composition includes glass powder, organic carrier and silver powder. The molar ratio of PbO and TeO2 in the glass powder is 0.4 to 0.8, and the grain size of silver powder is 20 to 150 nm. By controlling the proportion and structure of these components, the solubility of glass powder to silver ions is enhanced, and an excellent silver silicon contact structure is formed during the sintering process.

Benefits of technology

A conductive electrode structure with low resistance and low composite with a p-type doped polysilicon layer is realized, and the photoelectric conversion efficiency of crystalline silicon solar cells is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120221152A_ABST
    Figure CN120221152A_ABST
Patent Text Reader

Abstract

The invention provides conductive paste, a conductive electrode, a preparation method and a crystalline silicon solar cell. The conductive paste comprises the following components by weight: 3-7wt% of glass powder; 9-15 wt% of an organic carrier; 78 to 88 wt% of silver powder; the glass powder comprises the following components according to the amount of substance: 24-36 mol% of PbO; teO2: 40 to 60 mol%; siO2: 0 to 10 mol%; bi2O3: 0 to 10 mol%; 0-16 mol% of an alkali metal oxide; wherein the molar ratio of the PbO to the TeO2 is 0.4 to 0.8; and the grain size of the silver powder is 20-150nm. By controlling the adding proportion of PbO and TeO2 in the glass powder, the solubility of the glass powder to silver ions is enhanced, and meanwhile, the high-temperature fluidity and corrosivity of the glass powder are balanced; and by controlling the grain size of the silver powder, the silver powder and the glass powder have matched sinterability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of photovoltaic devices, and particularly relates to a conductive paste, a conductive electrode and a preparation method thereof, and a crystalline silicon solar cell. Background Art

[0002] An important technological breakthrough in crystalline silicon solar cells is the use of the tunnel oxide passivated contact structure (TOPCon), which significantly improves the open-circuit voltage (Voc) and cell efficiency of crystalline silicon solar cells. For the TOPCon passivated contact structure, the adapted metallization technology is crucial. The metallization paste is applied to the surface of the cell by screen printing, penetrates the surface passivation layer through high-temperature sintering, and then forms an electrical contact with the underlying polycrystalline silicon (poly-Si) layer. However, for p-type doped polycrystalline silicon (p-doped poly silicon, hereinafter referred to as p-poly), since its main carriers are holes, it is difficult for silver ions to be reduced to form a large amount of silver crystals on p-poly, and the electrical contact resistance between the formed electrode structure and p-poly is too high, resulting in a large efficiency loss. Therefore, finding an adapted metallization paste to solve the electrical contact required for p-poly TOPCon type crystalline silicon solar cells is a problem that needs to be solved currently. Summary of the Invention

[0003] The purpose of this application is to provide a conductive paste, a conductive electrode and a preparation method thereof, and a crystalline silicon solar cell, aiming to solve the problem that the conductive paste of the existing p-poly TOPCon type crystalline silicon solar cell affects the photoelectric conversion efficiency of the crystalline silicon solar cell.

[0004] The first embodiment of this application provides a conductive paste, which includes the following components by weight:

[0005] Glass powder: 3-7 wt%;

[0006] Organic carrier: 9-15 wt%;

[0007] Silver powder: 78-88 wt%;

[0008] The glass powder includes the following components by amount of substance:

[0009] PbO: 24-36 mol%;

[0010] TeO2: 40-60 mol%;

[0011] SiO2: 0-10 mol%;

[0012] Bi2O3: 0-10 mol%;

[0013] Alkali metal oxide: 0-16 mol%;

[0014] Among them, the molar ratio of the PbO to the TeO2 is 0.4 to 0.8; the grain size of the silver powder is 20 to 150 nm.

[0015] In some embodiments, the silver powder is spherical silver powder, and the D 50 particle size of the spherical silver powder is 0.5 to 4 μm.

[0016] In some embodiments, the alkali metal oxide includes at least one of Li2O and Na2O.

[0017] In some embodiments, in terms of amount of substance, the glass powder further includes the following components:

[0018] Fluoride: 0 to 5 mol%;

[0019] Silver oxide: 0 to 5 mol%;

[0020] Transition metal oxide: 0 to 5 mol%.

[0021] In some embodiments, the fluoride includes at least one of PbF and BiF3.

[0022] In some embodiments, the silver oxide includes at least one of AgO and Ag2O.

[0023] In some embodiments, the transition metal oxide includes at least one of ZnO, WO3, and MoO3.

[0024] The second embodiment of the present application provides a conductive electrode, including:

[0025] A semiconductor substrate, the semiconductor substrate includes a substrate, a tunneling layer, a p-type doped polysilicon layer, and a passivation layer which are stacked, and the p-type doped polysilicon layer is located between the tunneling layer and the passivation layer;

[0026] A first conductive structure, the first conductive structure penetrates through the passivation layer and forms an electrical connection with the p-type doped polysilicon layer, and the first conductive structure is formed by the conductive paste in any of the above embodiments.

[0027] In some embodiments, silver grains are embedded on one side of the p-type doped polysilicon layer close to the passivation layer, and the embedding depth of the silver grains is 1 to 250 nm.

[0028] In some embodiments, the substrate includes an n-type doped semiconductor substrate.

[0029] The third embodiment of the present application provides a method for preparing a conductive electrode, including the following steps:

[0030] Provided is a semiconductor substrate, which includes a substrate, a tunneling layer, a p-type doped polysilicon layer, and a passivation layer that are stacked. The p-type doped polysilicon layer is located between the tunneling layer and the passivation layer;

[0031] Print the conductive paste in any of the above embodiments on at least a part of the surface of the passivation layer;

[0032] Sinter the semiconductor substrate and the conductive paste, so that the conductive paste etches and penetrates the passivation layer during sintering to form a first conductive structure that is electrically connected to the p-type doped polysilicon layer, thereby obtaining the conductive electrode.

[0033] In some embodiments, the step of printing the conductive paste on at least a part of the surface of the passivation layer further includes:

[0034] Print the conductive paste on at least a part of the surface of the passivation layer in a patterned form.

[0035] The fourth embodiment of the present application provides a crystalline silicon solar cell, which includes the conductive electrode in any of the above embodiments, or the crystalline silicon solar cell includes the conductive electrode prepared by the preparation method in any of the above embodiments.

[0036] In some embodiments, the crystalline silicon solar cell includes a tunneling oxide passivation contact structure.

[0037] In some embodiments, the structure of the crystalline silicon solar cell is a double-sided TOPCon passivation contact cell or a TBC fully passivated contact back contact cell.

[0038] The present application provides a conductive paste, which includes the following components by weight: glass powder: 3-7 wt%; organic carrier: 9-15 wt%; silver powder: 78-88 wt%; the glass powder includes the following components by amount of substance: PbO: 24-36 mol%; TeO2: 40-60 mol%; SiO2: 0-10 mol%; Bi2O3: 0-10 mol%; alkali metal oxide: 0-16 mol%; wherein, the molar ratio of PbO to TeO2 is 0.4-0.8; the grain size of the silver powder is 20-150 nm. By controlling the addition ratio of PbO and TeO2 in the glass powder, the solubility of the glass powder in silver ions is enhanced while balancing the high-temperature fluidity and corrosiveness of the glass powder; on the other hand, by controlling the grain size of the silver powder, the silver powder has good crystallinity, so that it has ideal sinterability and conductivity matching the glass powder in the subsequent sintering process, realizes an excellent metallization effect of the conductive paste on p-poly, and further realizes a conductive electrode structure with low resistance and low recombination with the p-type doped polysilicon layer. Description of the Drawings

[0039] To more clearly illustrate the technical solutions in the embodiments of the present application, the following will briefly introduce the accompanying drawings required for the description of the embodiments. Obviously, the accompanying drawings in the following description are only some embodiments of the present application. For those skilled in the art, without creative efforts, other accompanying drawings can also be obtained based on these drawings.

[0040] Figure 1 It is a cross-sectional view of the conductive electrode provided by the embodiment of the present application;

[0041] Figure 2 It is a cross-sectional view of an n-TOPCon cell prepared with the conductive electrode provided by the embodiment of the present application;

[0042] Figure 3 It is a cross-sectional view of a TBC cell prepared with the conductive electrode provided by the embodiment of the present application;

[0043] Figure 4 It is a SEM cross-sectional view of the conductive electrode made of the conductive paste provided by Embodiment 1 of the present application;

[0044] Reference numerals: 10 - semiconductor substrate, 101 - substrate, 102 - first tunneling layer, 103 - p-type doped polysilicon layer, 104 - first passivation layer, 105 - second tunneling layer, 106 - n-type doped polysilicon layer, 107 - second passivation layer, 20 - first conductive structure, 30 - second conductive structure. Detailed implementation manners

[0045] The following will clearly and completely describe the technical solutions in the embodiments of the present application in conjunction with the accompanying drawings in the embodiments of the present application. Obviously, the described embodiments are only some embodiments of the present application, rather than all embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative efforts belong to the scope of protection of the present application.

[0046] In the description of the present application, it should be understood that the orientation or positional relationship indicated by the terms "upper", "lower", "top", "bottom", "inner", "outer", etc. is based on the orientation or positional relationship shown in the accompanying drawings. It is only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be construed as a limitation to the present application. In the description of the present application, "a plurality" means two or more, and at least one means one, two or more, unless otherwise clearly and specifically defined.

[0047] An important technological breakthrough in crystalline silicon solar cells is the use of tunnel oxide passivated contacts (TOPCon) structures, which significantly improve the open-circuit voltage (Voc) and cell efficiency of crystalline silicon solar cells, such as technologies like n-TOPCon cells and TOPCon back contact (TBC) cells. For the TOPCon passivated contact structure, a suitable metallization technology is crucial. The inventors found that the metallization paste can be applied to the surface of the cell by screen printing, penetrate the surface passivation layer through high-temperature sintering, and then form an electrical contact with the underlying poly-Si layer. The metallization requirement for the TOPCon passivated contact structure is to achieve good electrical contact while ensuring that its passivation effect is not damaged, in order to achieve higher photoelectric conversion efficiency.

[0048] The composition of the conductive paste, especially the glass powder and silver powder used in the paste composition, plays a crucial role in the metallization process. The glass powder needs to locally etch the surface passivation layer during high-temperature sintering so that silver can form an electrical contact with the underlying silicon substrate or polysilicon. For the p-poly layer, since the main carriers of p-poly are holes, and silver ion reduction requires free electrons, it is difficult for silver ions to be reduced on p-poly to form a large amount of silver crystals; if the silver-aluminum paste used for boron-diffused emitter metallization of n-TOPCon cells (i.e., adding aluminum powder to the silver paste) is used, the silver-aluminum barbs formed during sintering will penetrate the p-poly layer, resulting in serious damage to the passivation effect of the TOPCon structure and a significant loss of cell efficiency.

[0049] Based on this, the inventors found through research that by balancing the ratio of PbO and TeO2 in the glass powder and controlling the grain size of the silver powder, it is possible to achieve efficient electrical contact with the p-poly layer while ensuring the passivation effect of the TOPCon structure.

[0050] The first embodiment of this application provides a conductive paste, which includes the following components by weight:

[0051] Glass powder: 3 - 7wt%;

[0052] Organic carrier: 9 - 15wt%;

[0053] Silver powder: 78 - 88wt%.

[0054] Among them, the glass powder and silver powder are solid components in the conductive paste; the organic carrier is the dispersed phase in the conductive paste and provides printing performance, including one or more components such as polymers, surfactants, thickeners, thixotropic agents, and binders that can endow functional properties. The sum of the weight percentages of each component in the conductive paste is 100%.

[0055] Each component in the conductive paste will be described separately below.

[0056] glass powder

[0057] In some embodiments, the glass powder refers to a composition containing one or more types of anions and cations. When heated, specifically, when sintered at high temperature, the glass powder has the ability to flow. The glass powder can be crystalline or partially or completely vitreous or amorphous.

[0058] In some embodiments, the glass powder of this embodiment can be understood as a composition having a glass component. The mass percentage of the glass powder in the total weight of the conductive paste is 3 wt% to 7 wt%. Specifically, the mass percentage of the glass powder in the total weight of the conductive paste can be any value among 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt% or any value within the range composed of any two of these values.

[0059] In some other embodiments, the mass percentage of the glass powder in the total solids of the conductive paste is 2.5 wt% to 6.5 wt%, and can also be 3 wt% to 6 wt%; it can further be 3.5 wt% to 5.5 wt%; it can further be 4 wt% to 5 wt%.

[0060] It can be understood that the adjustment of the proportion of the glass powder in the conductive paste needs to ensure that the sum of the weight percentages of each component in the conductive paste is 100%. The components of the glass powder directly affect its fusibility, fluidity, and etchability. Therefore, the components of the glass powder need to have a good balance to achieve an excellent carrier recombination effect.

[0061] In some embodiments, the glass powder includes the following components in terms of amount of substance:

[0062] PbO: 24 - 36 mol%;

[0063] TeO2: 40 - 60 mol%;

[0064] SiO2: 0 - 10 mol%;

[0065] Bi2O3: 0 - 10 mol%;

[0066] Alkali metal oxides: 0 - 16 mol%.

[0067] In the following description, unless otherwise specified, "mol%" of the content of each component of the glass frit represents the mole percentage calculated in terms of oxide conversion.

[0068] It is understandable that the molar percentage of PbO in the glass powder can be any value among 24 mol%, 25 mol%, 26 mol%, 27 mol%, 28 mol%, 29 mol%, 30 mol%, 31 mol%, 32 mol%, 33 mol%, 34 mol%, 35 mol%, 36 mol% or any value within the range formed by any two of these values. The molar percentage of TeO2 can be any value among 40 mol%, 42 mol%, 44 mol%, 46 mol%, 48 mol%, 50 mol%, 52 mol%, 54 mol%, 56 mol%, 58 mol%, 60 mol% or any value within the range formed by any two of these values. The molar percentage of SiO2 can be any value among 0 mol%, 2 mol%, 4 mol%, 6 mol%, 7 mol%, 10 mol% or any value within the range formed by any two of these values. The molar percentage of Bi2O3 can be any value among 0 mol%, 2 mol%, 4 mol%, 6 mol%, 8 mol%, 10 mol% or any value within the range formed by any two of these values. The molar percentage of alkali metal oxide can be any value among 0 mol%, 2 mol%, 4 mol%, 6 mol%, 8 mol%, 10 mol% or any value within the range formed by any two of these values.

[0069] The composition of the glass powder has a significant impact on the process of the conductive paste forming a conductive structure during high-temperature sintering. Specifically, during high-temperature sintering, the glass powder melts to form a glass melt, and the glass melt can dissolve the silver in the conductive paste. In the cooling stage after sintering, the silver ions dissolved in the glass melt reach a supersaturated state and precipitate out again in the form of metallic silver, forming silver particles in the glass layer or embedding into the polysilicon layer to form silver crystals.

[0070] Taking this application as an example, during the high-temperature sintering process, the glass powder containing PbO and TeO2 begins to melt to form a glass melt and can dissolve the surrounding conductive metal into the glass melt. During the cooling process, the silver ions dissolved in the glass melt reach a supersaturated state and precipitate out again in the form of metallic silver, forming silver particles or silver crystals embedded in the polysilicon layer. Therefore, from a mechanistic perspective, a specific glass powder composition is required to increase the solubility of silver ions in the glass melt during the sintering process, enhance the supersaturated precipitation ability of silver ions, thereby promoting the growth of a large number of silver crystals in the p-poly layer after sintering and forming a good conductive electrode structure.

[0071] Among them, PbO is a glass intermediate used to enhance the corrosiveness of the glass powder. The addition amount of PbO can regulate the etching of the passivation layer covering the surface of the boron-diffused polysilicon layer, so that the conductive paste can locally open the passivation layer during the high-temperature sintering process. PbO is also an intermediate glass former that can be incorporated into the glass network, and the residual PbO will exist outside the glass framework as a glass modifier. However, excessive PbO will etch too much of the passivation layer, affecting the passivation effect of the crystalline silicon solar cell, and further affecting the photoelectric conversion efficiency of the crystalline silicon solar cell.

[0072] TeO2, as another glass intermediate, similar to PbO, helps to improve the high-temperature fluidity of the glass powder. For the composition of the glass powder of the p-poly metallization paste, it is necessary to achieve very good fluidity at high temperatures and excellent wettability with the polished crystalline silicon surface. Then, during the sintering process, the melted glass can quickly diffuse on the silicon wafer surface and etch the surface passivation layer. The glass powder with high fluidity and high wettability containing TeO2 and PbO can promote the formation of a large-area thin glass layer, thus promoting the precipitation of silver to form silver crystals and achieving more contact sites with the p-poly layer.

[0073] Bi2O3 is a glass intermediate. Both Bi2O3 and PbO have corrosiveness, but the corrosiveness of Bi2O3 is weaker than that of PbO. Bi2O3 is used in combination with PbO to adjust the etching ability of the glass powder on the passivation layer. Similarly, excessive Bi2O3 will etch too much of the passivation layer, affecting the passivation effect of the crystalline silicon solar cell, and further affecting the photoelectric conversion efficiency of the crystalline silicon solar cell. In addition, since the corrosiveness of PbO is stronger than that of Bi2O3, replacing a part of PbO with Bi2O3 in the composition of the glass powder can adjust the corrosion ability to meet the effect of low carrier recombination, thereby improving the open-circuit voltage and photoelectric conversion efficiency of the crystalline silicon solar cell.

[0074] SiO2 is a glass former used to adjust the glass transition temperature Tg and high-temperature fluidity of the glass powder. Appropriate addition can stabilize the glass phase, increase the melting point of the glass powder, and reduce the fluidity. SiO2 can also improve the weather resistance of the glass and adjust the reaction ability with the substrate. Silicon atoms form a tetrahedral SiO4 with four oxygen atoms and are connected to other tetrahedrons through bridging oxygen ions, which can enhance the stability of the glass powder and reconcile the corrosiveness of the glass melt to the passivation layer. The formed network structure can greatly increase the stability of metal cations (i.e., Ag + ) to enhance the stability of the glass melt and reconcile the corrosiveness of the glass melt to the passivation layer.

[0075] In some embodiments, the molar ratio of PbO to TeO2 is 0.4 to 0.8.

[0076] Since the lack of electrons in the p-poly layer inhibits the formation of silver crystals on the silicon surface, it is necessary to design a glass frit with high solubility for silver ions at high temperatures to achieve a large amount of silver ions dissolved in the glass melt, and then to achieve a high degree of supersaturation during sintering and cooling for the rapid precipitation of a large number of silver crystals, promoting the formation of more silver-silicon contact structures. The inventors found that increasing the content of TeO2 in the glass frit can enhance the solubility of silver ions in the glass melt. This is because TeO2 has a special crystal structure. In the glass system, it can interact with other components in the glass frit and change the network structure of the glass. TeO2 can exist in structural units such as [TeO4] tetrahedra and [TeO3] triangular pyramids, and form chemical bonds with other atoms in the glass network through oxygen atoms, thus providing more space and sites for the entry and dissolution of silver ions. In addition, Te atoms have a certain electronegativity, and the chemical bonds formed by them with oxygen atoms have a certain polarity, thereby increasing the solubility of silver ions in the glass melt.

[0077] On the other hand, the glass frit must have appropriate etching ability to etch the passivation layer. The etching ability of TeO2 is weaker than that of PbO. Therefore, it is necessary to control the ratio of PbO / TeO2 within an appropriate range to obtain balanced fluidity and etching ability of the glass melt.

[0078] It can be understood that the molar ratio of PbO and TeO2 refers to the ratio of the amount of substance of PbO in the glass frit to the amount of substance of TeO2 in the glass frit. The value of the molar ratio of PbO and TeO2 can be any value among 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8 or the range between any two values. When the molar ratio of PbO / TeO2 satisfies the above value range, the glass frit has relatively balanced fluidity, etching ability and solubility for silver ions.

[0079] In some embodiments, the alkali metal oxide includes at least one of Li2O and Na2O. The alkali metal oxide is used to control the corrosiveness of the glass frit so that the glass melt formed by the glass frit during high-temperature sintering can locally open the passivation layer to ensure the passivation effect of the crystalline silicon solar cell, and thus ensure the photoelectric conversion efficiency of the crystalline silicon solar cell.

[0080] In some embodiments, by amount of substance, the glass frit further includes the following components:

[0081] Fluoride: 0-5 mol%;

[0082] Silver oxide: 0-5 mol%;

[0083] Transition metal oxide: 0-5 mol%.

[0084] It is understandable that the molar percentage content of fluoride in the glass powder can be any value among 0 mol%, 1 mol%, 2 mol%, 3 mol%, 4 mol%, 5 mol% or a range between any two values. By adding fluoride, the Tg of the glass powder can be further reduced, while the fluidity of the glass frit at high temperature can be improved, and the thermal stability of the glass powder can be enhanced.

[0085] In some embodiments, the fluoride includes at least one of PbF and BiF3.

[0086] It is understandable that the molar percentage content of silver oxide in the glass powder can be any value among 0 mol%, 1 mol%, 2 mol%, 3 mol%, 4 mol%, 5 mol% or a range between any two values. Since silver ions are contained in silver oxide, adding additional silver oxide to the glass frit can increase the content of silver ions in the glass, thereby further promoting the precipitation and formation of silver crystals and achieving more contact sites with the p-poly layer.

[0087] In some embodiments, the silver oxide includes at least one of AgO and Ag2O.

[0088] It is understandable that the molar percentage content of transition metal oxide in the glass powder can be any value among 0 mol%, 1 mol%, 2 mol%, 3 mol%, 4 mol%, 5 mol% or a range between any two values. The addition of transition metal oxide can adjust the glass transition temperature Tg and the high-temperature fluidity of the glass powder, and can also be used as a component to improve the weather resistance of the glass powder.

[0089] In some embodiments, the transition metal oxide includes at least one of ZnO, WO3, and MoO3.

[0090] silver powder

[0091] It is understandable that the silver powder in the present application can be elemental silver metal, silver alloy powder, silver oxide, silver salt, and mixtures thereof, and may further include those derived from silver oxide (Ag2O or AgO) or silver salts such as AgCl, AgNO3, AgOOCCH3 (silver acetate), AgOOCF3 (silver trifluoroacetate), Ag3PO4 (silver orthophosphate), or mixtures thereof. As a conductive component, silver powder has excellent processability and high conductivity compared to metals such as gold, copper, nickel, and their alloys.

[0092] In some embodiments, the mass percentage of silver powder in the total solids of the conductive paste is 78% to 88%. Specifically, the mass percentage of silver powder in the total solids of the conductive paste can be any value or the range between any two values among 78%, 79wt%, 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%.

[0093] In some other embodiments, the mass percentage of silver powder in the total solids of the conductive paste is 79wt% to 84wt%, and can also be 84wt% to 88wt%; can further be 87wt% to 88wt%; can further be 80wt% to 88wt%.

[0094] It can be understood that the adjustment of the proportion of silver powder in the conductive paste needs to ensure that the sum of the weight percentages of each component in the conductive paste is 100%. The silver powder is used to play a conductive role after the crystalline silicon solar cell is formed.

[0095] In some embodiments, the silver powder has a polycrystalline structure, and the grain size of the silver powder is 20 to 150 nm.

[0096] During the sintering process of the glass powder, the silver powder will sinter into a dense structure, thus having excellent conductivity. However, the densification of the silver powder will affect the fluidity of the melted glass liquid, the etching of the passivation layer, and the distribution and thickness of the final glass layer. Therefore, the sintering or densification of the silver powder needs to be carried out after the glass powder starts to melt and flow, so as to avoid affecting the etching effect and the overall thickness of the glass layer. The inventors found through research that by controlling the grain structure of the silver powder, the crystallinity of the silver powder can be adjusted. The larger the grain size of the silver powder, the higher the crystallinity of the silver powder, and the higher crystallinity can increase the sintering temperature of the silver powder, so that the silver powder forms a densified structure after the glass powder starts to melt and flow.

[0097] It can be understood that the grain size of the silver powder is the statistical average value of all grains reflected by the diffraction peak of XRD. The value of the grain size (unit: nm) can be any value or the range between any two values among 20, 30, 50, 70, 90, 110, 130, 150. When the grain size of the silver powder meets the above value range, the silver powder has a relatively ideal crystallinity, increasing its sintering temperature, so as to match the components of the glass powder and achieve an ideal metallization effect for p-poly TOPCon.

[0098] In some embodiments, the grain size of the silver powder is 20 nm to 50 nm. It can be understood that the preferred grain size values (unit: nm) of the silver powder can be any value among 20, 24, 28, 32, 34, 38, 42, 46, 50 or the range between any two values. When the grain size of the silver powder meets the above preferred range, the crystallinity of the silver powder can be further optimized to match the components of the glass powder, avoiding the reduction of density and reactivity caused by too large grain size.

[0099] In some embodiments, silver can be provided as finely dispersed particles having the following forms, such as powder form, flake form, spherical form, rod form, granular form, nodular form, layered or coated form, other irregular forms, or mixtures thereof.

[0100] In some embodiments, the silver powder is spherical silver powder, and the D 50 particle size is 0.5 to 4 μm.

[0101] It can be understood that the D 50 particle size is the particle size corresponding to when the cumulative volume percentage of the silver powder reaches 50 wt%. The D 50 particle size values (unit: μm) of the spherical silver powder can be any value among 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4 or the range between any two values. Further preferably, the D 50 particle size of the spherical silver powder is 1.5 μm to 3.5 μm; more preferably, the D 50 particle size of the spherical silver powder is 2 μm to 3 μm; more preferably, the D 50 particle size of the spherical silver powder is 2 μm to 2.5 μm. The main function of the silver powder is to form a high-density silver crystal after sintering to provide good electrical conductivity for electrical contact with the polysilicon layer. When the D 50 particle size of the spherical silver powder meets the above value range, especially the preferred value range, the formed silver crystal can not only have good electrical contact and conductivity, but also inhibit agglomeration and ensure uniform dispersion of the silver powder.

[0102] In some embodiments, the silver powder can be in a coated or uncoated form; for example, it can be at least partially coated with a surfactant to facilitate processing. Suitable coating surfactants include, for example, stearic acid, palmitic acid, stearates, palmitates, and mixtures thereof. Other surfactants that can also be used include lauric acid, oleic acid, capric acid, myristic acid, linoleic acid, and mixtures thereof. Other surfactants that can also be used include polyethylene oxide, polyethylene glycol, benzotriazole, poly(ethylene glycol) acetic acid, and other similar organic molecules. Suitable counter-ions used in the coating surfactant include, but are not limited to, hydrogen, ammonium, sodium, potassium, and mixtures thereof. For example, silver can be coated with a phosphorus-containing compound.

[0103] organic carrier

[0104] In some embodiments, the organic carrier accounts for 9 wt% to 15 wt% of the total solids in the conductive paste. Specifically, the mass percentage of the organic carrier in the total solids of the conductive paste can be any value among 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt% or any value within the range composed of any two of these values.

[0105] In some embodiments, the organic carrier accounts for 11 wt% to 14 wt% of the total solids in the conductive paste. In some other embodiments, it can also be 9 wt% to 12 wt%. It can further be 12 wt% to 15 wt%.

[0106] In some embodiments, relative to the solids composed of silver powder and glass powder, the organic carrier serves as the liquid phase in the conductive paste to disperse the above-mentioned solids, so as to form a paste with a certain viscosity. The viscosity and rheology of the paste can not only enable the above-mentioned silver powder and glass powder to be stably dispersed therein for a long time, but also enable the conductive paste to be dispersed on the printing screen, and a desired pattern is coated on the surface of the passivation layer of the semiconductor substrate by means of screen printing.

[0107] In some embodiments, the organic carrier may include a polymer and an organic solvent. The polymer may include cellulose, resin, esters, etc. Cellulose includes cellulose resins such as methyl cellulose, ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, benzyl cellulose, propyl cellulose, nitrocellulose, or a mixture thereof. Resins include wood rosin, phenolic resin, acrylic resin, or a mixture thereof. Esters include polymethacrylates of lower alcohols, etc. Organic solvents may include terpineol, diethylene glycol butyl ether acetate, diethylene glycol ethyl ether acetate, propylene glycol diacetate, α-terpinene, β-terpinene, dibutyl phthalate, butyl carbitol, butyl carbitol acetate, hexylene glycol, etc.

[0108] In some embodiments, the organic carrier has a consistency and rheology suitable for printing methods, including but not limited to screen printing. The organic medium may also include other additives such as non-ionic surfactants, thixotropic agents, dispersants, rheological agents, etc., to adapt to the organic medium with different requirements.

[0109] In some embodiments, the glass powder can be prepared by using methods commonly used in the glass manufacturing field. For example, oxides corresponding to the composition ratio of the glass powder described in the embodiments are proportioned, mixed, added to a crucible (such as a platinum or ceramic crucible), heated to a peak temperature (e.g., 800 °C to 1400 °C), and held for a period of time to melt the oxides together. The molten material can then be quenched in any suitable manner, including but not limited to passing it between counter-rotating stainless steel rollers to form a sheet with a thickness of 0.25 mm to 0.50 mm, pouring it onto a thick stainless steel plate, or pouring it into water. Then, the resulting glass frit is ground using common grinding techniques to form a powder with a particle size of 0.5 μm to 2 μm. Common grinding techniques include, for example, jet milling, ball milling, sand milling, or planetary milling.

[0110] In some embodiments, the preparation method of the conductive paste may include: proportioning and stirring and dispersing according to the components of the conductive paste described in the embodiments, then dispersing and grinding with a three-roll mill to a fineness of less than 10 μm, and then further filtering. The adjustment of the ratio of the glass powder, conductive metal, and organic carrier needs to ensure that the sum of the mass percentages of each component in the conductive paste is 100%.

[0111] conductive electrode

[0112] The second embodiment of the present application provides a conductive electrode, as Figure 1 shown, including:

[0113] A semiconductor substrate 10, the semiconductor substrate 10 includes a substrate 101, a first tunneling layer 102, a p-type doped polysilicon layer 103, and a first passivation layer 104 arranged in a stacked manner, and the p-type doped polysilicon layer 103 is located between the first tunneling layer 102 and the first passivation layer 104;

[0114] A first conductive structure 20, the first conductive structure 20 penetrates the first passivation layer 104 and forms an electrical connection with the p-type doped polysilicon layer 103, and the first conductive structure 20 is formed by sintering the conductive paste in any of the above embodiments.

[0115] It can be understood that the first conductive structure 20 can form an electrical connection with the p-type semiconductor with lower carrier recombination and lower resistance. The p-type semiconductor can be the p-type doped polysilicon layer 103, and the substrate 101 can be an n-type doped semiconductor substrate.

[0116] In some embodiments, silver grains are embedded on one side of the p-type doped polysilicon layer 103 close to the first passivation layer 104, and the embedding depth of the silver grains is 1 to 250 nm.

[0117] It can be understood that the value of the embedding depth of the silver grains (unit: nm) can be any value among 1, 25, 50, 75, 100, 125, 150, 175, 200, 225, 250 or the range between any two values. The embedding of the silver grains in the p-type doped polysilicon layer 103 can achieve excellent electrical contact between the first conductive structure 20 and the p-type doped polysilicon layer 103, and thus effectively collect holes in the p-type doped polysilicon layer 103; however, when the silver grains are embedded too deeply in the p-type doped polysilicon layer 103, it will cause excessive damage to the p-type doped polysilicon layer 103, resulting in excessive carrier recombination loss. Therefore, it is necessary to control the embedding depth of the silver grains while satisfying the embedding of the silver grains in the p-type doped polysilicon layer 103. When the embedding depth of the silver grains satisfies the above value range, it can achieve excellent electrical contact between the first conductive structure 20 and the p-type doped polysilicon layer 103 while ensuring the transport efficiency of carriers in the p-type doped polysilicon layer 103.

[0118] In some embodiments, the substrate 101 includes an n-type doped semiconductor substrate.

[0119] The third embodiment of the present application provides a method for preparing a conductive electrode, including the following steps:

[0120] S1. Provide a semiconductor substrate 10, which includes a substrate 101, a first tunneling layer 102, a p-type doped polysilicon layer 103, and a first passivation layer 104 arranged in a stacked manner, and the p-type doped polysilicon layer 103 is located between the first tunneling layer 102 and the first passivation layer 104;

[0121] S2. Print a conductive paste on at least a part of the surface of the first passivation layer 104;

[0122] S3. Sinter the semiconductor substrate 10 and the conductive paste, so that the conductive paste etches and penetrates the first passivation layer 104 during the sintering process to form a first conductive structure 20 that is electrically connected to the p-type doped polysilicon layer 103, and obtain a conductive electrode.

[0123] In some embodiments, the step of printing the conductive paste on at least a part of the surface of the first passivation layer 104 further includes:

[0124] Print the conductive paste on at least a part of the surface of the first passivation layer 104 in a patterned form.

[0125] It can be understood that the specific steps of printing the conductive paste on at least a part of the surface of the first passivation layer 104 in a patterned form include:

[0126] The conductive paste is applied to at least a part of the surface of the first passivation layer 104 facing away from the p-type doped polysilicon layer 103 in a desired patterned form. During the high-temperature sintering process, the glass powder in the conductive paste melts to form a glass melt, and the glass melt dissolves the metal in the conductive paste. Specifically, part of the silver powder is dissolved by the glass melt, and the remaining silver powder densifies during the sintering process. Corrosive oxides such as PbO and TeO2 in the glass powder cause corrosion and etching of the first passivation layer 104 to open and penetrate the first passivation layer 104 in a local area, forming a through hole (not shown in the figure) that penetrates the first passivation layer 104 in the thickness direction on the first passivation layer 104. The patterning method can be screen printing. It can be understood that the conductive paste involved in this embodiment is used as a fine grid for the p-type doped polysilicon surface or region of the conductive electrode in a crystalline silicon solar cell.

[0127] solar cell

[0128] The fourth embodiment of the present application provides a crystalline silicon solar cell, which includes the conductive electrode in any of the above embodiments, or the crystalline silicon solar cell includes the conductive electrode prepared by the preparation method in any of the above embodiments.

[0129] In some embodiments, the crystalline silicon solar cell includes a tunneling oxide layer passivation contact structure. This solar cell utilizes the tunneling oxide layer as a charge transport channel and a surface passivation layer to improve the efficiency and performance of the cell. The solar cell structure based on the TOPCon structure has low electron reflection and surface recombination, and at the same time has a high photoelectric conversion efficiency and low electron defects.

[0130] In some embodiments, the structure of the crystalline silicon solar cell is a double-sided TOPCon passivation contact cell or a TBC fully passivated contact back contact cell.

[0131] In some embodiments, as Figure 2 shown, the structure of the crystalline silicon solar cell is a double-sided TOPCon passivation contact cell, including a semiconductor substrate 10, a first conductive structure 20, and a second conductive structure 30. The first conductive structure 20 and the second conductive structure 30 are respectively disposed on opposite sides of the semiconductor substrate 10. Among them, the semiconductor substrate 10 includes: a substrate 101; a first tunneling layer 102, a p-type doped polysilicon layer 103, and a first passivation layer 104 stacked on one side of the substrate 101; and a second tunneling layer 105, an n-type doped polysilicon layer 106, and a second passivation layer 107 stacked on the other side of the substrate 101.

[0132] The first tunneling layer 102 and the second tunneling layer 105 can be formed by the tunneling oxide passivation contact method. The first tunneling layer 102 and the second tunneling layer 105 can be ultra-thin silicon dioxide layers. The first tunneling layer 102 is located on the front side of the substrate 101, and the substrate 101 can be an n-type doped semiconductor substrate; the p-type doped polysilicon layer 103 can be a boron-doped polysilicon layer, which is located on the surface of the first tunneling layer 102 away from the substrate 101. The second tunneling layer 105 is located on the back side of the substrate 101, and the substrate 101 can be an n-type doped semiconductor substrate; the n-type doped polysilicon layer 106 can be a phosphorus-doped polysilicon layer, which is located on the surface of the second tunneling layer 105 away from the substrate 101.

[0133] The first conductive structure 20 is prepared by using the metallized conductive paste provided in the embodiments of the present application. The conductive paste composition is applied to at least a part of the surface of the first passivation layer 104 in a desired patterned form. During the sintering process, the conductive paste penetrates the first passivation layer 104 to obtain the first conductive structure 20 that forms an electrical connection with low carrier recombination with the p-type doped polysilicon layer 103.

[0134] The second conductive structure 30 can be prepared by using the metallized silver paste applied to p-type or n-type crystalline silicon cells on the market, such as Solamet PV6NL silver paste. The silver paste is applied to at least a part of the surface of the passivation film in a desired patterned form. During the sintering process, the glass powder in the silver paste etches and penetrates the second passivation layer 107, so as to form an electrical contact with the n-type doped polysilicon layer 106, so as to form the second conductive structure 30 in the form of a conductive metal contact.

[0135] In other embodiments, as Figure 3 shown, the crystalline silicon solar cell is a back-contact cell with TBC full passivation contact, including a semiconductor substrate 10, a first conductive structure 20 and a second conductive structure 30. The first conductive structure 20 and the second conductive structure 30 are arranged on the same side of the semiconductor substrate 10. Among them, the semiconductor substrate 10 includes: a substrate 101; a first tunneling layer 102, a p-type doped polysilicon layer 103 and a first passivation layer 104 stacked on one side of the substrate 101; and a second tunneling layer 105, an n-type doped polysilicon layer 106 and a second passivation layer 107 stacked on the same side of the substrate 101.

[0136] The substrate 101 can be an n-type doped semiconductor substrate. The first tunneling layer 102 can be an ultra-thin silicon dioxide layer located on the back surface of the substrate 101. The p-type doped polysilicon layer 103 can be a boron-doped polysilicon layer located on the surface of the first tunneling layer 102 away from the substrate 101. The first passivation layer 104 is deposited on the surface of the p-type doped polysilicon layer 103 away from the first tunneling layer 102. The first conductive structure 20 penetrates at least a part of the first passivation layer 104 and forms an electrical connection with the p-type doped polysilicon layer 103.

[0137] The second tunneling layer 105 can be an ultra-thin silicon dioxide layer, also located on the back surface of the substrate 101. The n-type doped polysilicon layer 106 can be a phosphorus-doped polysilicon layer located on the surface of the second tunneling layer 105 away from the substrate 101. The second passivation layer 107 is deposited on the surface of the n-type doped polysilicon layer 106 away from the second tunneling layer 105. The second conductive structure 30 penetrates at least a part of the second passivation layer 107 and forms an electrical connection with the n-type doped polysilicon layer 106.

[0138] An embodiment of the present application provides a method for manufacturing a solar cell, including:

[0139] 1) Provide a semiconductor substrate 10, and the structure of the semiconductor substrate 10 is as Figure 2 or Figure 3 shown;

[0140] 2) Apply the metallized conductive paste provided by the embodiment of the present application on the surface of the first passivation layer 104 of the p-face or p-region of the semiconductor substrate 10. Specifically, apply the metallized conductive paste in a patterned form on at least a part of the surface of the passivation layer. The patterning method can be screen printing;

[0141] 3) Apply the metallized silver paste on the surface of the second passivation layer 107. Specifically, apply the metallized silver paste in a patterned form on at least a part of the surface of the passivation layer. The patterning method can be screen printing;

[0142] 4) Sinter the semiconductor substrate 10, the metallized conductive paste, and the metallized silver paste, so that the metallized conductive paste etches and penetrates the passivation layer during sintering to form the first conductive structure 20 that makes an electrical connection with the p-type doped polysilicon layer 103, and the metallized silver paste etches and penetrates the passivation layer during sintering to form the second conductive structure 30 that makes an electrical connection with the n-type doped polysilicon layer 106.

[0143] The serial numbers of the above steps are not regarded as limiting the order of the steps.

[0144] In some embodiments, after sintering, a method of further optimizing laser-enhanced contact can be carried out. This is a method of using laser in the manufacturing process of solar cells to improve the electrical contact of metallization paste. The basic principle of laser-enhanced contact improvement technology is to utilize a large number of carriers generated by the laser. Using a bias voltage to guide these carriers through the formed metallization contact points, and using the heat energy generated by the current to improve the contact effect and uniformity. It can improve the uniformity of electrical contact, reduce contact defects, thereby improving the efficiency and reliability of solar cells. In this technology, the injection amount of carriers can be controlled by parameters such as laser power and time to achieve better contact uniformity and improvement effect.

[0145] In some embodiments, the laser scanning time is from 1 ms to 100 ms, and the reverse voltage is from 5 V to 20 V. Using the laser-enhanced contact optimization technology to process the conductive structure can reduce the contact resistance, which is more conducive to the increase of open-circuit voltage and the improvement of efficiency.

[0146] The following will make the following descriptions of the conductive paste, conductive electrode and preparation method, and crystalline silicon solar cell provided by the present application in combination with specific embodiments:

[0147] The component contents of the glass powder in Examples 1 to 19 and the glass materials in Comparative Examples 1 to 3 are shown in Tables 1 and 2. The PbO / TeO2 in Table 1 refers to the molar ratio of PbO and TeO2 in the glass powder. The sum of the components in the glass powder of each example and each comparative example is 100 mol%. Among them, the PbO and TeO2 in Examples 1 to 19 cover different molar percentages and molar ratios of the two; Examples 7 to 10 adjust the high-temperature physical properties of the glass powder by adding different ratios and types of transition metal oxides; Examples 11 to 19 adjust the fluidity and corrosiveness of the glass powder by adding SiO2 and adjusting different contents; Examples 16 to 17 additionally add Ag2O on the basis of adding SiO2 to increase the overall silver ion content in the conductive paste. In Comparative Example 1, the low content of PbO results in a low molar ratio of PbO and TeO2; in Comparative Example 2, the high content of PbO results in a high molar ratio of PbO and TeO2; in Comparative Example 3, the content of TeO2 is low.

[0148] Table 1

[0149]

[0150]

[0151] Table 2

[0152] Mol% PbF <![CDATA[Al2O3]]> <![CDATA[B2O3]]> ZnO <![CDATA[WO3]]> <![CDATA[MoO3]]> <![CDATA[Ag2O]]> Example 1 / / / / / / / Example 2 / / / / / / / Example 3 / / / / / / / Example 4 / / / / / / / Example 5 / / / / / / / Example 6 / / / / / / / Example 7 / 1 / / 5.5 / / Example 8 / / 1 5.5 / / / Example 9 / / 1 / 5.5 / / Example 10 / / 1 / / 5.5 / Example 11 / / / / / / / Example 12 / / / / / / / Example 13 / / / / / / / Example 14 / / / / / / / Example 15 / / / / / / / Example 16 / / / / / / 1.5 Example 17 / / / / / / 3 Example 18 1.5 / / / / / / Example 19 3 / / / / / / Comparative Example 1 / / / / / / / Comparative Example 2 / / / / / / / Comparative Example 3 / 1 1.5 5 2.5 / /

[0153] Select appropriate silver powder, and prepare metallized conductive pastes with the glass frits of Examples 1 to 19 and Comparative Examples 1 to 3 in Table 1. Obtain corresponding Examples 20 to 38 and Comparative Examples 4 to 6. In the following examples, the composition of the conductive paste can be adjusted accordingly to obtain suitable properties that meet the requirements. For example, the amount of the glass frit can be easily adjusted according to the final use requirements. The specific content is shown in Table 3, where the silver powder has an average grain size of 36 nm and a D 50 spherical silver powder with a particle size of 2.1 μm. The organic components specifically include: 1.5 wt% ethyl cellulose, 1.5 wt% polyvinyl butyral copolymer (PVB), 1.6 wt% diethylene glycol butyl ether acetate, 0.3 wt% silicone oil, 0.15 wt% Duomeen TDO (a non-ionic surfactant belonging to the amine oxide category), 0.15 wt% Brij L4 (a non-ionic surfactant belonging to the polyoxyethylene alcohol category), 0.4 wt% Thixotrol plus (a rheological agent), 2.8 wt% Ethoxylated Alcohol C12, 0.6 wt% dibasic acid ester, and the rest is solvent. The specific preparation process of the conductive paste composition is as follows: Weigh and mix the above components, stir and disperse them, then disperse and grind them with a three-roll mill to a fineness of less than 10 μm, and then further filter to obtain the formulations of the components in Examples 20 to 38 and Comparative Examples 4 to 6 as shown in Table 3.

[0154] Evaluation of the contact performance of the conductive electrode:

[0155] Apply an N-type simulated silicon wafer with a p-type doped polycrystalline silicon layer passivation contact structure for metallization printing and sintering, and then measure the contact resistance Rc.

[0156] Metallization: Screen-print the specified metallized conductive paste on the p-poly surface of the p-poly TOPCon simulated silicon wafer and then perform high-temperature sintering (in a Meyer sintering furnace, with the furnace temperature of 18 zones).

[0157] Contact resistance measurement: After sintering, cut the wafer into strips with a width of 1 cm along the direction perpendicular to the silver grid line with a laser, and then measure the contact resistance Rc with a PV Tools TLM measurement system.

[0158] The detection results of the contact performance of the p-poly conductive electrodes prepared with the conductive pastes in Examples 20 to 38 and Comparative Examples 4 to 6 are shown in Table 3.

[0159] Table 3

[0160]

[0161]

[0162] Examples 20 to 38 are all within the preferred glass powder composition range disclosed in the present invention. From the experimental data, excellent contact resistance can be achieved.

[0163] Among them, the conductive electrode structure in Example 38 is as Figure 4 shown in the SEM cross-sectional view.

[0164] From Comparative Example 4, it can be seen that the PbO / TeO2 ratio of the glass powder is less than 0.4. This type of glass powder has good fluidity, but the corrosion resistance is too weak, resulting in a high contact resistance.

[0165] From Comparative Example 5, it can be seen that the PbO / TeO2 ratio of the glass powder is higher than 0.8. This type of glass powder has strong corrosion resistance, but weak fluidity, also resulting in a high contact resistance.

[0166] From Comparative Example 6, it can be seen that the content of TeO2 in the glass powder is less than 40 mol%. Although the PbO / TeO2 ratio is within the preferred range, its fluidity is still not ideal, resulting in a high contact resistance.

[0167] Silver powders of different sizes are selected and mixed with the glass powder provided in Example 3. Conductive pastes and conductive electrodes are prepared using the same steps as in Example 20. First, the particle size and grain size of the silver powder are detected. The detection methods are as follows:

[0168] Silver powder particle size test method: Particle size analyzer.

[0169] Silver powder grain size test method: Bruker D8 ADVANCE X-ray diffractometer (XRD)

[0170] a) XRD sample preparation method: The sample is loaded into the sample tray of the equipment, and the powder is leveled with a glass plate to ensure consistency with the plane of the sample tray, and then it enters the equipment for testing;

[0171] b) XRD test conditions: Scanning from 10° to 90°, speed 6° / min.

[0172] Grain size calculation: First, the phase is matched based on the XRD data for qualitative analysis, and then the curve is fitted through software analysis, and the grain size of the sample is calculated by integration.

[0173] Through the above method, Comparative Examples 7 to 8 of Examples 39 to 46 are obtained. The silver powder sizes and the contact performance test results of the p-poly conductive electrodes in Comparative Examples 7 to 8 of Examples 39 to 46 are shown in Table 4.

[0174] Table 4

[0175]

[0176] As can be seen from Table 4, under the same glass powder and addition amount, in Comparative Examples 7-8, due to the relatively small grain size of the silver powder, the contact resistance Rc of the finally prepared crystalline silicon cell is also significantly higher. Therefore, the value range of the grain size of the silver powder provided in this application plays an important role in the metallization of crystalline silicon cells.

[0177] The conductive paste, conductive electrode and preparation method, and crystalline silicon solar cell provided in the embodiments of the present application have been introduced in detail above. Specific examples are used in the present application to elaborate on the principle and implementation manner of the present application. The description of the above embodiments is only used to help understand the technical solution and its core idea of the present application; those of ordinary skill in the art should understand that they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements on some of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A conductive paste, characterized in that: The components include the following by weight: Glass powder: 3-7wt%; Organic carrier: 9-15wt%; Silver powder: 78-88wt%; The glass powder comprises the following components by amount: PbO: 24-36 mol%; TeO2: 40-60 mol%; SiO2: 0-10 mol%; Bi2O3: 0-10mol%; Alkali metal oxide: 0-16 mol%; Wherein, the molar ratio of the PbO to the TeO2 is 0.4-0.8; and the grain size of the silver powder is 20-150 nm.

2. The conductive paste according to claim 1, characterized in that: The silver powder is spherical silver powder, and the D 50 The particle size is 0.5~4μm.

3. The conductive paste according to claim 1, characterized in that: The alkali metal oxide includes at least one of Li2O and Na2O.

4. The conductive paste according to claim 1, characterized in that: The glass powder further comprises the following components by amount: Fluoride: 0-5 mol%; Silver oxide: 0-5 mol%; Transition metal oxide: 0 to 5 mol%.

5. The conductive paste according to claim 4, characterized in that: The fluoride includes at least one of PbF and BiF3.

6. The conductive paste according to claim 4, characterized in that: The silver oxide includes at least one of AgO and Ag2O.

7. The conductive paste according to claim 4, characterized in that: The transition metal oxide includes at least one of ZnO, WO3 and MoO3.

8. A conductive electrode, characterized in that: include: A semiconductor substrate (10), the semiconductor substrate (10) comprising a stacked substrate (101), a first tunneling layer (102), a p-type doped polysilicon layer (103) and a first passivation layer (104), the p-type doped polysilicon layer (103) being located between the first tunneling layer (102) and the first passivation layer (104); A first conductive structure (20), wherein the first conductive structure (20) penetrates the first passivation layer (104) and forms an electrical connection with the p-type doped polysilicon layer (103), and the first conductive structure (20) is formed by the conductive paste according to any one of claims 1 to 7.

9. A conductive electrode according to claim 8, characterized in that: Silver grains are embedded on one side of the p-type doped polysilicon layer (103) close to the first passivation layer (104), and the embedding depth of the silver grains is 1 to 250 nm.

10. The conductive electrode according to claim 8, characterized in that The substrate (101) comprises an n-type doped semiconductor substrate.

11. A method for preparing a conductive electrode, characterized in that: The steps include: A semiconductor substrate (10) is provided, wherein the semiconductor substrate (10) comprises a stacked substrate (101), a first tunneling layer (102), a p-type doped polysilicon layer (103) and a first passivation layer (104), wherein the p-type doped polysilicon layer (103) is located between the first tunneling layer (102) and the first passivation layer (104); Printing a conductive paste on at least a portion of the surface of the first passivation layer (104), wherein the conductive paste is the conductive paste according to any one of claims 1 to 7; The semiconductor substrate (10) and the conductive paste are sintered, so that the conductive paste etches and penetrates the first passivation layer (104) during the sintering process to form a first conductive structure (20) electrically connected to the p-type doped polysilicon layer (103), thereby obtaining the conductive electrode.

12. The method for preparing a conductive electrode according to claim 11, characterized in that: The step of printing the conductive paste on at least a portion of the surface of the first passivation layer (104) further comprises: The conductive paste is printed in a patterned form on at least a portion of the surface of the first passivation layer (104).

13. A crystalline silicon solar cell, characterized in that: The crystalline silicon solar cell comprises the conductive electrode as claimed in any one of claims 8 to 10, or the crystalline silicon solar cell comprises the conductive electrode prepared by the preparation method as claimed in any one of claims 11 and 12.

14. The crystalline silicon solar cell according to claim 13, characterized in that: The crystalline silicon solar cell comprises a tunneling oxide layer passivation contact structure.

15. The crystalline silicon solar cell according to claim 13, characterized in that: The structure of the crystalline silicon solar cell is a double-sided TOPCon passivated contact cell or a TBC fully passivated contact back contact cell.

Citation Information

Cited By

  • N-region conductive paste adaptive to TBC solar cell, preparation method of N-region conductive paste, and TBC solar cell

    CN121416157A